Cohabitation With Atlantic Salmon (Salmo salar) Affects Brain Neuromodulators But Not Welfare Indicators in Lumpfish (Cyclopterus lumpus) - Staven, Fredrik Ribsskog; Gesto, Mauel; Iversen, Martin Haugmo; Andersen, Per; Patel, Deepti Manjari; Nordeide, Jarle Tryti; Kristensen, Torstein (Frontiers in Physiology, 2022)
publishedVersion